pH-influenced self-assembled stealth nanoscaffolds encapsulating memantine for treatment of Alzheimer’s disease - Rani V.; Verma R.; Kumar K.; Chawla R. (My University, 2025)
Alzheimer’s disease (AD) is the most common neurological disorder characterized by the accumulation of β-amyloid peptides. The only medication used to treat moderate-to-severe AD progression is memantine. In this study, polyethylene glycol (PEG)-coated poly D, L-lactic-co-glycolic acid (PLGA) nanostructures were prepared, as their self-assembling ability helps to penetrate the drug at disease sites with altered pH range (5.7–6.8) due to AD. Drug and polymer interaction studies by FTIR showed no interaction among them, and the thermal properties of drugs, polymers, and nanostructures tell us about their melting behaviour, thermal degradation, and glass transition temperatures. Characterization of prepared self-assembled nanoscaffolds signifies that the acquired properties such as size, structure, surface charges, zeta-potential, stability, thermal properties, biodegradability, biocompatibility, swelling ability, encapsulation, and drug loading provide an efficient therapeutic activity to the nanostructures for the treatment of AD. In addition, parallel artificial membrane permeability assay (PAMPA) has revealed the paracellular transport mechanism of nanoscaffolds across the blood–brain barrier. In vitro release kinetics showed a sustained release pattern exhibiting the Korsmeyer–Peppes drug release kinetic model with a correlation coefficient (R 2) value of 0.9905, which describes the drug release pattern from a polymeric system. In vitro enzymatic studies demonstrated the inhibition activity of nanostructures on acetylcholinesterase (AChE), butyrylcholinestrase (BUChE), and β-secretase enzyme which prevents the breakdown of acetylcholine, butyrylcholine, and amyloid precursor protein, and retention of these neurotransmitters constituted the primary therapeutic strategy for AD. Also, behavioural studies have shown a significant (p<0.05) improvement in cognition behaviour among nanostructures-administered animal groups in a scopolamine-induced amnesia model. The designed nanocarrier can also accelerate the treatment strategies for AD by incorporating stem cells and self-assembled nanoscaffolds that could provide a 3D extracellular matrix to facilitate neuron regeneration, hence improving cognition behaviour effectively. © 2023, Indian Academy of Sciences.